Investigating the influence of elements in pocket parks on the psychological restoration of young people: a study from Guiyang and Chongqing in Southwest China - Ma, Geng; Pellegrini, Paola; Ma, Jiaqi; Shi, Linfeng (Taylor and Francis, 2024)
In an era marked by rapid pace and demanding work schedules, young individuals frequently experience mental exhaustion and emotional downturns, exacerbating mental health issues. Recognizing this, prior studies have underscored the significant role of pocket parks in fostering emotional rejuvenation. However, previous research has primarily suggested that green natural elements in pocket parks positively influence restorative effects, without thoroughly examining the restorative power of different natural elements. Furthermore, there has been a lack of systematic analysis to quantify the impact of both natural elements and activities in pocket parks on their restorative effects. This research adopts a quantitative approach to explore the interaction between psychological attributes and the restorative impacts of various natural elements within pocket parks. It also considers the influence of socio-demographic factors, ultimately proposing an evaluation model to assess these spaces’ psychological restoration capabilities. Focusing on Guiyang and Chongqing as study locations, the research utilized 20 photographs to represent typical elements within pocket parks. Analysis of these images led to the identification of nine critical elements. Participants provided insights into how these factors relate to psychological characteristics and their subsequent restorative effects by responding to five carefully designed questions. The analysis revealed that amenities for relaxation and sports play a pivotal role in enhancing restorative outcomes and influencing psychological traits. Additionally, the effect of natural elements on restoration varied; while trees and water bodies positively contributed to restoration, shrubs and lawns were found to have a less significant effect. The study concludes by introducing an evaluation model that identifies the primary built environment factors influencing restoration. The results of this study are intended to guide the redesign of pocket parks and inform policy-making processes.